The effect of managing expectations on job satisfaction of public Schools teachers in the Directorate of Education of the Kasbah of Irbid District - Alsheikh, Nawal Mohammed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal aimed to reveal the level of management expectations of public school teachers in the Directorate of Education of the Kasbah of Irbid District and its impact on their job satisfaction, where the problem of the study lies in the presence of weakness of school teachers with regard to their level of job satisfaction, so it is important to study this variable and reveal the factors affecting it. Therefore, this study seeks to test the following hypothesis: There is no statistically significant effect at the level of significance of expectations management on job satisfaction among public school teachers in the Directorate of Education of the Kasbah Irbid District. In order to achieve the objective of the study, the descriptive analytical method was used by developing a questionnaire as a tool for collecting data included (36) items divided into two dimensions: managing expectations dimension, and job satisfaction dimension, and it was applied to a sample of (324) teachers from the Directorate of Education and Irbid Kasbah. That the study sample members’ perceptions of the degree to which school teachers have to manage expectations came to a medium degree, and that the study sample members’ perceptions of job satisfaction came to a medium degree as well. The results also showed that there is a statistically significant effect at the significance level (α≤0.05) for managing expectations on job satisfaction for public school teachers in the Directorate of Education in Irbid Kasbah. In light of the results reached, the study recommended the need to enhance the level of expectation management among school teachers in Irbid Kasbah, through holding training courses and workshops to train them on the skill of managing expectations in the light of realism, communicating with transparency, defining goals and desired results accurately, and selecting means and methods clearly.
Keywords: Managing Expectations; Job Satisfaction; Teachers; Jordan